A new catalyst for the synthesis of 2-substituted perimidines catalysed by FePO4. Issue 1 (1st January 2017) - Behbahani, F.K.; Golchin, Fatemeh M.
Abstract: The reaction of 1, 8-diaminonaphthalene with aromatic aldehydes gave 2-substituted perimidines in the presence of FePO4 as a versatile, green and reusable catalyst at room temperature.